Resilience, perceived mistreatment and mental health in medical residents - Zárate Camargo, Natalia; Marván, María Luisa; Rosas Santiago, Francisco Javier (Horizonte Sanitario, 2024)
Objective: This study aims to analyze the influence of resilience and perceived mistreatment on mental health and the satisfaction with the residencyMaterials and Methods: An observational cross-sectional study carried out with 147 medical residents who answered the Depression, Anxiety and Stress Scale (DASS-21), the Walgnid 14-item Resilience Scale and questions related to satisfaction with the residency, perception of received mistreatment and deterioration in mental health. Correlation and logistic binary regression analyses were made. The study was endorsed by an Ethics in Research Committee.Results: Resilience did not correlate with any of the variables of interest, on the other hand, participants of first and second year who perceived mistreatment had a higher probability of showing high stress and to perceive a greater deterioration in mental health. In students of second and third year, perceived mistreatment negatively predicted the satisfaction with residency. There were no significant results when analyzing participants of fourth year.Conclusions: The results of this study question the role of resiliency as a protective factor for mental health in the face of adverse circumstances experienced by medical residents during their training and emphasize the negative impact of mistreatment in the formative process of future specialists. Keywords: Workplace Violence; Resilience; Mental Health; Internship and Residency.